Planktonic drivers of carbon transformation during different stages of the spring bloom at the Patagonian Shelf-break front, Southwestern Atlantic Ocean - Gilabert, Azul Sabina (2025)
The processes involved in the carbon cycle are essential for marine trophic networks and global climate regulation. Interactions within the microbial loop play key roles in carbon transformation and transport across the food web. The Argentine Patagonian Shelf in the Southwestern Atlantic Ocean is a hotspot for carbon sequestration. However, our understanding of microbial impacts on carbon cycling in this area remains limited. This study examines the microbial community structure and its role in the carbon transformation during a progression of the spring bloom along the Patagonian shelf-break and adjacent ocean. This progression was studied in a latitudinal track where we observed a gradient of Dissolved Organic Matter (DOM) complexity. In the northern area, the bloom termination was characterised by low Chlorophyll-a concentrations, with smaller organisms (Synechococcus) dominating the autotrophic plankton biomass, and high viral concentrations. DOM showed high humification and aromaticity, indicating an intensified microbial activity by heterotrophic bacteria that followed the production of phytoplankton-derived DOM. In the southern area, high Chlorophyll-a was mainly attributed to large protist plankton, accompanied by abundant heterotrophic bacteria and bioavailable DOM from recent phytoplankton blooms. These results showed that during bloom termination, bacterial production of refractory compounds significantly immobilises carbon, suggesting a potential pathway for carbon sequestration. Additionally, data suggest high carbon retention on the shelf side of the front by microbial transformation and efficient trophic transfer within the microbial community, while the side influenced by the Malvinas Current, presents high carbon export by advection and a higher degree of unutilised carbon from bacterial origin. These findings highlight rapid shifts in carbon dynamics driven by microbial successions during different bloom phases.